Studi Antropologi-Teologi “Ritus Arumbai Raja” di Ullath-Saparua - Sostenes Chaterina Dias (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to describe the Arumbai Raja Rite, a religious style built on the cultural foundation of the Ullath community. In this case, the Ullath people transformed their myth of nobility and gave birth to a new mechanism in maintaining the order of royal relations. In that sense, the implementation of the Arumbai Raja Rite in Ullath remains framed in an effort to maintain brotherly relations and maintain the balance of the cosmos. The research used is a type of qualitative research, by examining the Arumbai Raja Rite. The practice of cultural rituals in the ullath community contains an important goal for the communal existence of the ullath community. This mechanism is also a social mechanism through which the Ullath people are able to integrate permanently with the Iha and Tuhaha communities. This is proof that the brotherhood between them that was built by their ancestors is an ideal type that is to be achieved and maintained continuously. The results of the research on the views of the Arumbai Raja Rite were then analyzed in culture, customs and rites and resulted in the findings: The Arumbai Raja ritual in Ullath has values contained in it, namely proof of true brotherhood. and a symbol of nature conservation. Besides this ritual is almost extinct, and in all countries on the island of Saparua, only Ullath country that still maintains and carries out this ritual.